Mulching in coffee growing: effects on productivity, maturation, grain shape and beverage quality (Research, Society and Development, 2020)
Polyethylene mulching can be used as a promising technique in the cultivation of perennial tilths, reducing the incidence and costs of weed management. The purpose was to evaluate the productive and quality parameters of coffee considering the use of polyethylene mulching with different colors and widths in the municipality of Monte Carmelo, Minas Gerais. The experiment was conducted at the Federal University of Uberlandia, Campus Monte Carmelo. The planting of the crop, cultivar Topázio MG-1190, happened in December 2016, using spacing of 3.5 m between rows and 0.6 m between plants. The experimental delimitation was in randomized blocks, with four blocks and five treatments: white / black mulching, width 1.20 m; 1.40 m width white / black mulching; silver / black mulching width 1.20 m; silver / black mulching width 1.40m and no mulching. In 2019, for the first crop year, productivity, the percentage of green, cane-green, cherry, raisins and dried fruits, sensory analysis and the classification of grains in terms of size and format. Pearson correlations were also estimated between the percentage variables of green and cherry fruits, productivity and number of defects. It was verified that the use of mulching caused an increase of 16.9 bags ha-1 compared with the control treatment, producing coffees that reached a special drink standard according to SCAA protocol. The use of plastic cover sped the fruits maturation and decreased the percentage of medium mocha fruits, emphasizing the potential use of this technology in the formation of coffee crops.